Kampen om stenalderen. Antropologiske bud på vor oprindelse i fortid og nutid - Høiris, Ole; Liversage, David (Jysk Arkæologisk Selskab, 1996)
Fight over the Stone Age Both in our own past and in human evolution and history the Stone Age is regarded as a period and a state of being in which the basal traits in our nature and in our cultural and social existence were established. Therefore the Stone Age is in many ways about ourselves and our own identity as human beings. How it is portrayed is therefore an important matter. The article presents briefly in chronological order the most important of the anthropological theories that for more than a century have turned attention to this primordial age. These theories (the scientific classical evolutionistic, the diffusionism or cultural history of historiography, the cultural ecology and neo-evolutionism of cultural science, and the Marxism of social science) each in is way sets the bounds of how this origin and the laws governing its development could be expressed in a present-day perspective -i.e. how we have used science in an attempt to express our own time's "myth of origin" in a way which either elevated and supported our present civilization or viewed it critically. A number of central themes for construction of the past according to different theories are presented. In the case of classical evolutionism this is the controversy over the Christian story of the Creation and the relativation of Christianity, the construction of the origin of the family, and the paradisic contra the animaline character of original existence. In cultural history the relative importance of migration and cultural diffusion, concepts of mankind and the world, religion, family structure, and Danish arctic studies were discussed. Next came the theory of technoenvironmental determinism, the family structure of hunting societies, their political and economic organization, and the concept of the primordial existence as a paradisic life of plenty held by cultural ecology and neo-evolutionism. As a special subject the attack of women's anthropology on the male-dominated concept of the hunter is examined. Last considered are the problems Marxism has in finding class or other antitheses in huntergatherer societies as starting point for the required logic of evolution from the huntergatherer to the tribal stage, when classes and class struggles were easier to argue for. The Marxist conception of this primary communist society's social and family organisation was described in a perspective critical of capitalism. In the ensuing sections one of the most important subjects of debate is taken up -the question how far hunter-gatherer society is representative of our own past. Postmodern criticism is briefly described, after which the issue taken by world system theory with the opinion that these societies were a survival is examined with the Bushmen as example. Lastly the background for the formation of our own idea of hunter-gatherer society as being our own origin because it best answered to the negation of the agricultural societies that were the hypothetical source of the analyses. Ole Høiris